PERUBAHAN PENGALIHAN HAK MILIK MENJADI HAK PAKAI WARGA NEGARA ASING YANG BERDOMISILI DI INDONESIA BERDASARKAN PERATURAN MENTERI AGRARIA NO.29 TAHUN 2016 - Hendy Sutanto (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractThe reason the writer chose the title of Perubahan Hak Milik Menjadi Hak Pakai Warga Negara Asing is due to the contradictory rules between UUPA and PERMEN ATR / Head of BPN No.29 of 2016 which allows foreigners to have land rights in Indonesia.The research method used by the writer is a descriptive normative legal research, finding the transfer regulation of ownership rights over land because of buying and selling. Legal materials used are primary legal materials and secondary legal materials. Legal materials collection techniques used are through literature studies in the form of books, documents, and archives as well as collecting legal materials with interview techniques. Data analysis is carried out with interpretation of concrete eventsThe result of this research is the legal consequences that can arise due to the sale and purchase of land rights to foreigners who are not subject to the law of Property Right, based on the theory of legal material, the foreigner can have legal certainty to have the Right Property but limited only to be changed into Right of Use with a certain time limit after the sale and purchase and then to use the Right to Use for register it to the BPN.The Conclusion that the writer got based on the research results obtained 2 (two) conclusions, namely the first transition or transfer of rights is a legal act aimed at transferring rights from one party to another party and in this case the subject is a foreigners. With the PERMEN ATR / Head of BPN No.29 of 2016, the process of transfer of Property Right can be done directly to the Right of Use and the second due to the law based on the theory of legal material, the foreigner can have legal certainty to have the right property but limited only to be changed into Right of Use with a certain time limit after the sale and purchase and then registered with the BPN